EFFECTS OF TAXATION ON CORPORATE INVESTMENT IN NIGERIA (Journal of Contemporary Issues in Accounting, 2022)
This paper evaluates the effect of tax aggressiveness on corporate investment expenditure in Nigeria based on a sample of 119 non-financial firms quoted in Nigeria stock exchange from 2010 to 2017. The outcomes measured by estimating pooled ordinary least squares, random and fixed effects models. The corporate tax aggressiveness indicators are tax saving, effective tax rate, book tax gap, temporary tax difference with firm size as control variable. Findings, among others, reveal that tax aggressiveness has a statistically significant influence on corporate investment expenditure in Nigeria. It provides evidence that tax aggressiveness positive and statistically significant coefficients of the tax aggressiveness variables, particularly tax saving and effective tax rate which maintained a consistent positive and statistically significant relation to corporate investment expenditure across all model specifications. In other words, increase in tax saving and effective tax rate boost total investment expenditure, investment maintenance expenditure and new investment expenditure in Nigeria. Other findings are that book tax gap shows a negative impact on corporate investment expenditure. This is because managers reduces taxable income to increases investment maintenance expenditure. For the control variables, total assets boost corporate investment expenditure.
Keywords: aggressiveness; tax; tax saving; effective tax rate; book tax gap; temporary tax difference; investment expenditure